Import tariffs of trading partners: Evidence from three West Balkan countries - Safet Kurtović; Blerim Halili; Nehat Maxhuni (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper aims to examine the effect of reducing the import tariffs of trading partners on total and individual exports of products from three countries of the Western Balkans and individually observed for each country. In order to investigate the potential effect, this paper applied the gravity equation and the GMM model system dynamic data estimation. The research is based on aggregate and non-aggregate approach. Within the aggregate approach for the three countries of the Western Balkans, the reduction of import simple average tariff rate (SAT) and weighted average tariff (WAT) rate have a positive effect on the growth of total and individual exports of products. Within the non-aggregate approach for each country individually, the reduction in imports of SAT and WAT rates also have a positive effect on the growth of total and individual exports of products from Albania and Serbia, while this effect is weak for FYR Macedonia.
Keywords: F11; F14; F15; 330; tariffs; exports; products; preferential tariffs; trade agreements